A Novel Mechanism of PPARγ Regulation of TGFβ1: Implication in Cancer Biology - Chang Ho Lee; Hyung Don Kim; Sang Mi Shin; Sang Geon Kim (PPAR Research)
Peroxisome proliferator-activated receptor-γ (PPARγ) and retinoic acid X-receptor (RXR) heterodimer, which regulates cell growth and differentiation, represses the TGFβ1 gene that encodes for the protein involved in cancer biology. This review will introduce the novel mechanism associated with the inhibition of the TGFβ1 gene by PPARγ activation, which regulates the dephosphorylation of Zf9 transcription factor. Pharmacological manipulation of TGFβ1 by PPARγ activators can be applied for treating TGFβ1-induced pathophysiologic disorders such as cancer metastasis and fibrosis. In this article, we will discuss the opposing effects of TGFβ on tumor growth and metastasis, and address the signaling pathways regulated by PPARγ for tumor progression and suppression.